Hemoglobin J-Singapore [α79(EF8)Ala→Gly, GCG>GGG] in a pregnant Thai woman - Sitthichai Panyasai (2018)
© 2018, Medical Association of Thailand. All rights reserved. Hemoglobin [Hb] J-Singapore [α79(EF8)Ala→Gly, GCG>GGG] is a very rare α-globin chain variant. In the present study, the authors reported, for the first time, the Hb J-Singapore in a 31-year-old Thai pregnant woman. She was seen by an obstetrician at her fifteenth week of gestation. Based on routine antenatal thalassemia and hemoglobinopathy screening, her Hb analysis was performed by high performance liquid chromatography [HPLC] and the abnormal Hb peak with a value of 23.6% was observed at the retention time of 1.83 minutes. The abnormal Hb peak was also found at zone 12 of capillary electrophoresis [CE] electrophoregram, which was similar to the peak of Hb Bart’s and Hb J-Buda. The direct DNA sequencing revealed the GCG>GGG mutation at codon 79 of α2-globin gene as previously described for Hb J-Singapore. In addition, the developed multiplex allele specific polymerase chain reaction [MAS-PCR] showed the 632 bp amplified fragment from Hb J-Singapore allele. Thus, the knowledge and understanding of this hemoglobinopathy will be used to assist in diagnosis, management, and counseling for needed patients.